Perlindungan Hukum Terhadap Pihak Yang Beritikad Baik Dalam Perjanjian Lisensi Merek Menurut Undang-Undang No.15 Tahun 2001 Tentang Merek - Tajuddin Noor (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
License Institution is one of the most important A license agency is one of the most important parts to implement HAKI (Intellectual Property Rights) of trademark and services. The implementation of the brand licensing agreement in Indonesia is regulated by the Branding Act No. 15, 2001. License is a permit given by a registered brand owner to other parties with an agreement based on the granting of rights (not transfer of rights) to use the brand, either for the whole or part of the type of goods and / or services that are registered in certain time and conditions. In licensing, the law provides legal protection to those who are well-liked. This provision constitutes a fundamental application of legal protection to the parties concerned. The legal protection of those parties is regulated in the Branding Act, Article 48, 2001. Keywords: Legal Protection, Good-willed Parties, Brand Licensing Agreement